2017
DOI: 10.3126/kumj.v13i2.16788
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Nutritional Status of Rural School going Children in Kavre District

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 10 publications
4
4
1
Order By: Relevance
“…However different studies such as study conducted in 2014 in Kaski district of Nepal, further analysis of Demographic and Health survey 2008 in Ghana 2015 documented the lower prevalence of underweight 15.3% and 13.8% respectively among adolescents [24],[29]. In spite of this, most of the studies conducted in rural areas of different countries such as study conducted in 2015 in Kavre district of Nepal among rural school going adolescent girls of 9–16 years, cross-sectional study conducted by Bisai, Bose, Ghosh and De, 2011 among rural school children aged 11–18 years of West Bengal, India and data from the Global School-based Student Health Survey (GSHS) in seven African countries between 2006 and 2010, by Taru, Hesham, David and Jason in 2014 from randomly selected schools going adolescents of 11–17 years showed the prevalence of underweight among adolescents were high 31.98%, 28.3% and 31.9% respectively than the present study [22],[30],[31].The variation of underweight in different study might be due to the difference in study setting of different schools, different age group of adolescents included in the study and methodologies applied in the study.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…However different studies such as study conducted in 2014 in Kaski district of Nepal, further analysis of Demographic and Health survey 2008 in Ghana 2015 documented the lower prevalence of underweight 15.3% and 13.8% respectively among adolescents [24],[29]. In spite of this, most of the studies conducted in rural areas of different countries such as study conducted in 2015 in Kavre district of Nepal among rural school going adolescent girls of 9–16 years, cross-sectional study conducted by Bisai, Bose, Ghosh and De, 2011 among rural school children aged 11–18 years of West Bengal, India and data from the Global School-based Student Health Survey (GSHS) in seven African countries between 2006 and 2010, by Taru, Hesham, David and Jason in 2014 from randomly selected schools going adolescents of 11–17 years showed the prevalence of underweight among adolescents were high 31.98%, 28.3% and 31.9% respectively than the present study [22],[30],[31].The variation of underweight in different study might be due to the difference in study setting of different schools, different age group of adolescents included in the study and methodologies applied in the study.…”
Section: Discussioncontrasting
confidence: 44%
“…According to Global School Based Student Health Survey (GSHS) 2015, 10.9% (male 13.8%, female 8.1%) adolescent students were underweight, 6.7% (male 7.6%, female 5.8%) were overweight (heavy for their height) and 0.6% (male 0.8% and female 0.4%) of the school going adolescent were obese [21]. A cross-sectional study conducted among school going adolescent girls, 9–16 years studying in various schools in rural area of Kavre district, Nepal found that overall prevalence of underweight, stunting and thinness was 31.98%, 21.08% and 14.94% respectively [22]. In most developing countries, nutrition initiatives have been focusing on children and women, thus neglecting adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…This might be one of the reasons for low levels of thinness seen in our analysis, especially in the girls. The phenomenon where boys continue to gain height resulting in higher levels of thinness has also been seen in neighboring countries like Indonesia, Bangladesh and Nepal (11%, 19.6%, 37.8% in boys and 5%, 15.4% and 26.2% in girls) [36][37][38].…”
Section: Stunting and Its Impact On Estimates Of Thinnessmentioning
confidence: 82%
“…The prevalence of underweight, thinness and stunting among school children were 7.40%, 52.59% and 28.88% respectively. A similar type of study was conducted by Mansur et al, 12 reported the prevalence of underweight, thinness and stunting was 30.85%, 10.05% and 24.54% respectively. 12 Bose et al, 15 found 16.9% were underweight, 17.2% were stunting and 23.1% were thinness among children.…”
supporting
confidence: 59%
“…A similar type of study was conducted by Mansur et al, 12 reported the prevalence of underweight, thinness and stunting was 30.85%, 10.05% and 24.54% respectively. 12 Bose et al, 15 found 16.9% were underweight, 17.2% were stunting and 23.1% were thinness among children. 15 Similarly, the study done by Shivaprakash and Joseph 2014 reported the overall prevalence of underweight and stunting in the studied school children was 30.3% and 27.9% respectively.…”
supporting
confidence: 59%